From Crisis Adoption to Behavioral Continuity: Online Shopping Behavior of Indonesian Silver Consumers - Hery Maulana Arif (Journal Management & Economics Review (JUMPER), 2026)
The COVID-19 pandemic accelerated the global transition from conventional retail to digital commerce due to lockdowns and health concerns. This shift was particularly significant among silver consumers aged 55 years and above, many of whom adopted online shopping for the first time to access essential goods and services. Despite increasing digital adoption among older adults, existing studies mainly focus on younger generations and rarely examine the complete pre-purchase process, including product search and evaluation. This study aims to analyze the persistence of online shopping behavior among elderly consumers in the post-pandemic period and identify the psychological and technological factors influencing long-term digital adoption. A longitudinal prospective cohort approach is proposed by tracking silver consumers over 12–24 months using digital diaries, browser tracking, and periodic surveys. The findings indicate a substantial increase in online shopping frequency, digital payment adoption, and consumer intention to continue using e-commerce platforms after the pandemic. More than 75% of new online shoppers reported continued interest in digital purchasing behavior. The study concludes that digital trust, perceived security, and ease of platform use are critical factors sustaining online shopping continuity among elderly consumers, contributing to the emergence of a hybrid “new normal” consumption pattern.